OP43 Cardiovascular disease risk prevention in poor communities in sub-Saharan Africa: leveraging on community-driven participatory citizen science approach to co-design prevention advocacy strategies in Ethiopia, Malawi, and Rwanda. (26th August 2022) - Okop, Kufre; Lambert, Estelle; Getachew, Hailemichael; Hailu, Belachew; Kedir, Kiya; Howe, Rawleigh; Niyibizi, Jean; Bavuma, Charlotte; Rulisa, Stephen; Kasenda, Stephen; Crampin, Amelia; Levitt, Naomi
Abstract : Background: In sub-Saharan Africa (SSA) with high cardiovascular disease (CVD) burden ( (33 million death), population-based screening and prevention measures are unfortnately hampered by low levels of knowledge about CVD and associated risk factors, and inaccurate perceptions of severity of risk. This study aimed to explore CVD risk perceptions and to co-design community-specific advocacy and prevention strategies in the rural and urban SSA communities. Methods: We implemented community-driven participatory research in three SSA countries (Malawi, Ethiopia, and Rwanda), using a citizen science approach. We undertook community engagement, recruitment of citizen scientists (CSts), followed by Citizen Science semi-structured interviews, and collaborative results generation and knowledge co-creation. The results were then used to facilitate stakeholders' advocacy, and follow-up engagements in the project communities. Trained CSts supported the co-designing of data collection tools, explored CVD-related health risk (using a mobile app, EpiCollect), aggregated and analysed data collected in the form of photovoice and narratives to facilitate collaborative participation in community-engaged science and CVD risk prevention advocacy. Comparative data analysis was undertaken using parametric comparisons to determine the difference in the risk perceptions and advocacy strategies. Results: A total of 40 CSts were trained. These collected data from 138 participants (65% women) randomly sampled in 8 communities in the 3 countries. Data collected included participants demographics, 8–10 pictures from each participant, and the corresponding narratives about risk perception. About 74% of participants interviewed had self-reported of an history of a relative sick of CVD, with most (62%) reported in urban. Majority of rural and urban participants took pictures of things considered several potential risk factors to include cigarette, alcohol, salt, sugar, coffee, smoke, and poor-quality cooking oil; other risk factors mentioned were liter, poor sanitation, loss of job, and poor diet. Level of personal CVD risk perception was significantly influenced health seeking intentions. The majority (87%) of participants in the rural and urban Ethiopia preferred health risk to be presented using health-related graphics (visual aid), verbal message, and or audio voice. The urban participants wanted targeted 'short and brief' messages. In Malawi, the urban and rural participants preferred one-on-one discussion at community level, and peer-support. CSts were excited for the opportunity to lead as 'scientists' in their communities. In Rwanda and Ethiopia, there were probable uptake of research evidence by government, as district and MOH officials appreciated citizen scientists' work and made decision to utilise them in research intervention programmes. Conclusion: Participatory citizen science can foster community-driven science and co-designing of CVD risk prevention intervention in SSA settings.